Treatment of advanced emphysema with emphysematous lung sealant (AeriSeal) - Herth, Felix; Gompelmann, Daniela; Stanzel, F.; Bonnet, R.; Behr, J.; Schmidt, B.; Magnussen, H.; Ernst, Armin; Eberhardt, Ralf (Respiration, 2011)
Background: This report summarizes initial tests of an emphysematous lung synthetic polymer sealant (ELS) designed to reduce lung volume in patients with advanced emphysema.Objectives: The primary study objective was to define a therapeutic strategy to optimize treatment safety and effectiveness. Methods: ELS therapy was administered bronchoscopically to 25 patients with heterogeneous emphysema in an open-label, noncontrolled study at 6 centers in Germany. Treatment was performed initially at 2-4 subsegments. After 12 weeks, patients were eligible for repeat therapy to a total of 6 sites. Safety and efficacy were assessed after 6 months. Responses were evaluated in terms of changes from baseline in lung physiology, functional capacity, and health-related quality of life. Follow-up is available for 21 of 25 patients. Results: Treatment was well tolerated. There were no treatment-related deaths (i.e. within 90 days of treatment), and an acceptable short- and long-term safety profile. Physiological and clinical benefits were observed at 24 weeks. Efficacy responses were better among Global Initiative for Chronic Obstructive Lung Disease (GOLD) stage III patients [n = 14; change in residual volume/total lung capacity (ΔRV/TLC) = -7.4 ± 10.3%; Δ forced expiratory volume in 1 s (ΔFEV1) = +15.9 ± 22.6%; change in forced vital capacity (ΔFVC) = +24.1 ± 22.7%; change in carbon monoxide lung diffusion capacity (ΔDLCO) = +19.3 ± 34.8%; change in 6-min walk test (Δ6MWD) = +28.7 ± 59.6 m; change in Medical Research Council Dyspnea (ΔMRCD) score = -1.0 ± 1.04 units; change in St. George’s Respiratory Questionnaire (ΔSGRQ) score = -9.9 ± 15.3 units] than for GOLD stage IV patients (n = 7; ΔRV/TLC = -0.5 ± 6.4%; ΔFEV1 = +2.3 ± 12.3%; ΔFVC = +2.6 ± 21.1%; ΔDLCO = -2.8 ± 17.2%; Δ6MWD = +28.3 ± 58.4 m; ΔMRCD = 0.3 ± 0.81 units; ΔSGRQ = -6.7 ± 7.0 units). Conclusions: ELS therapy shows promise for treating patients with advanced heterogeneous emphysema. Additional studies to assess responses in a larger cohort with a longer follow-up are warranted.